Introduction: Symposium on Air Pollution - The Editors (Washington University Law Quarterly, 1968)
In this student-written Symposium on Air Pollution the Law Quarterly attempts to analyze generally the problems of governmental regulation of air pollution at all levels. For those unfamiliar with the technical aspects of air pollution, the symposium begins with a very basic consideration of the nature, sources and causes of contamination and possible abatement techniques. Successive notes discuss existing and proposed legislation and the effectiveness, appropriateness, and limitations of regulatory programs at the municipal, state, interstate, and federal levels. The last of these includes an explanation and evaluation of the Air Quality Act of 1967, the new federal program.
Keywords: Air pollution